Body Figure Idealization and Body Appearance Pressure in Fitness Instructors - Mathisen, Therese Fostervold; Aambø, Jenny; Bratland-Sanda, Solfrid; Sundgot-Borgen, Christine; Svantorp-Tveiten, Kethe; Sundgot-Borgen, Jorunn (Frontiers in Psychology, 2020)
Purpose: The fitness centers are settings for health promotion, yet may serve as a stage for counterproductive figure idealization. Such idealization may take the form of a drive towards the thin-, the muscular-, or lean body figure ideal, which all hold the potential to impel an experience of body appearance pressure and body dissatisfaction. The aim of this study was to explore figure idealization, body dissatisfaction, and experience of body appearance pressure (BAP) in fitness instructors. Methods and materials: Fitness instructors, 70 (23%) males and 236 (77%) females, were recruited through their Facility CEO and social media for a digital survey on mental health. Results are presented for body appreciation (BAS-2), body dissatisfaction (EDI-BD), drive for muscularity (DM), drive for leanness (DLS), questions on BAP, symptoms of eating disorders (EDE-q), and history of weight regulation and eating disorders (ED). Results: Attempts to gain body weight were reported by 17% of females and 53% of males, while 76% of males and females respectively, reported to have attempted weight reduction. Reasons for body weight manipulation were predominantly appearance related, and 10-20% reported disordered eating behavior. Mean BAS-2 and EDI-BD were acceptable, but 28% of females was above clinical cut-off in EDI-BD, and mean DLS were high in both sexes. In total 8% of females were above clinical cut-off in EDE-q, which corresponded well with the self-reported ED. About 90% of the sample perceived BAP to be a societal issue, and reported predominantly by customers and colleagues to be the cause of their personal experience of BAP. Less than 50% knew of any actions taken by their employer to reduce BAP. There were few differences according to profession or educational level. Conclusion: Fitness instructors report BAP to affect them negatively, which may put them at risk of impaired mental health. Educational level did not protect against figure idealization and BAP. To care for their employees and to optimize their position as a public health promoter, the fitness industry should target BAP in health promotion programs.